Investigating the Conformation of HER Membrane Proteins in Cells via Single Molecule and FLIM Microscopy - Martin-Fernandez, Marisa L.; Clarke, David T.; Hirsch, Michael; Needham, Sarah R.; Roberts, Selene K.; Rolfe, Daniel J.; Tynan, Chris J.; Webb, Stephen E.D.; Winn, Martyn; Domingues, Laura Zanetti (IntechOpen, 2012)
None